23 Tahun Penelitian Pada Pemposisian Pasar: Agenda Penelitian di Masa Depan - Cikal (Ekonomi dan Bisnis, 2024)
On a practical level, market positioning is critical to achieving competitive advantage, and thus the success of new ventures and entrepreneurs needs more relevant insights to help them gain a foothold in new or existing markets. The purpose of this paper is to carefully analyze and assess the current body of written work regarding the strategic act of positioning a product or brand in the market, thereby critically reassessing and re-evaluating the fundamental notion of positioning and ultimately establishing a more all-encompassing and thorough definition from an abstract and theoretical point of view. In this paper, the authors would like to explore past research related to market positioning in the Scopus database using the keywords “positioning marketing", marketing positioning”, "positioning”, and “strategic positioning” from 2000–2023 (23 years) using the criteria of “exclude and include,” and a total of 140 articles were obtained. Once analyzed, the literature review revealed that there is no coherent definition for positioning and that there is no common agreement among marketing experts and practitioners on the precise meaning of the concept. Therefore, a comprehensive definition of positioning covering the five underlying positioning perspectives (competition, gap/empty mind, consumer perception, differentiation, and advantage) is suggested. Keywords: Market Positioning, Positioning Strategy, Bibliometric Analysis.